Caring Professional Attitude Of nursing In Palliative Nursing Care - Edy Suprayitno; Raisa Farida Kafil (Interest : Jurnal Ilmu Kesehatan, 2021)
Background: Caring is an important part of nursing care. Caring is a behavior that interacts emotion with the patient's response. Purpose: This research aims to determine the caring behavior of nurses in providing palliative nursing care Methods: The research employed qualitative method (FGD), using hermeneutic phenomenology approach (n=7, chemotherapy nurses) and interview guide instruments. The data analysis used was Interpretative Phenomenology Analysis and has obtained ethics worthy of KEP UNISA Yogyakarta: 1342/KEP-UNISA/IX/2020 and KEP Yogyakarta Regional Public Hospital: 41/KEP/RSUD/X/2020. Results: Based on the results of the study, there are 2 major themes of professional caring attitudes of nurses in providing palliative care, that are the emotional closeness of nurses to patients and their families and an attitude full of empathy with a sense of humor. Conclusion: Nurses always provide nursing care in a professional caring manner to patients and their families by prioritizing comfort, emotional closeness and humor.